2018
DOI: 10.1097/md.0000000000011620
|View full text |Cite
|
Sign up to set email alerts
|

Three-point sign in subacute combined degeneration of the spinal cord

Abstract: Rationale:Subacute combined degeneration (SCD) of the spinal cord has been reported to have distinctive characteristics on magnetic resonance imaging (MRI), such as an “inverted V sign”, a “pair of binoculars sign”, and a “dot sign”. We report a 3-point sign as a novel MRI characteristic, expanding the spectrum of imaging signs for SCD.Patient concerns:A 64-year-old female vegetarian presented with a 3-month history of progressive numbness and weakness in the lower extremities.Diagnosis:Laboratory examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Abnormalities on MRI of SCDS patients have been identified to include distinctive characteristics such as an "inverted V sign," a "pair of binoculars sign," and a "dot sign" [8]. However, Jain et al [9] reported that only 11.1-36.7% of patients with SCDS showed marked abnormalities on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities on MRI of SCDS patients have been identified to include distinctive characteristics such as an "inverted V sign," a "pair of binoculars sign," and a "dot sign" [8]. However, Jain et al [9] reported that only 11.1-36.7% of patients with SCDS showed marked abnormalities on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…3 These may be the distinctive and prototypical 'inverted V' sign as well as the recently described 'three-point' sign. 3 However, isolated posterior column hyperintensity in the form of 'binocular sign' and 'dot' sign on MRI have also been described, albeit less commonly. 4 It is important to note that SACD may present with atypical clinical features.…”
Section: Discussionmentioning
confidence: 92%
“…Radiological features in SACD typically exhibit posterolateral signal change and are seen in 11%–37% of patients. 3 These may be the distinctive and prototypical ‘inverted V’ sign as well as the recently described ‘three-point’ sign. 3 However, isolated posterior column hyperintensity in the form of ‘binocular sign’ and ‘dot’ sign on MRI have also been described, albeit less commonly.…”
Section: Discussionmentioning
confidence: 93%
“…However, as observed in our patient, signal abnormalities are usually very distinctive when present. This often appears hyperintense on T2-weighted imaging but normal on T1-weighted imaging with an unremarkable or slight enhancement [ 6 ]. Other distinctive features such as an “inverted V sign,” a “pair of binoculars sign,” and a “dot sign” have also been identified on MRI [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%